Chitosan/siRNA functionalized titanium surface via a layer-by-layer approach for in vitro sustained gene silencing and osteogenic promotion - Song W (Dove Medical Press, 2015)
Wen Song,1,* Xin Song,2,* Chuanxu Yang,2 Shan Gao,2 Lasse Hyldgaard Klausen,2 Yumei Zhang,1 Mingdong Dong,2 Jørgen Kjems21State Key Laboratory of Military Stomatology, Department of Prosthetic Dentistry, School of Stomatology, The Fourth Military Medical University, Xi’an, People’s Republic of China; 2Interdisciplinary Nanoscience Center (iNANO), Aarhus University, Aarhus, Denmark*These authors contributed equally to this workAbstract: Titanium surface modification is crucial to improving its bioactivity, mainly its bone binding ability in bone implant materials. In order to functionalize titanium with small interfering RNA (siRNA) for sustained gene silencing in nearby cells, the layer-by-layer (LbL) approach was applied using sodium hyaluronate and chitosan/siRNA (CS/siRNA) nanoparticles as polyanion and polycation, respectively, to build up the multilayered film on smooth titanium surfaces. The CS/siRNA nanoparticle characterization was analyzed first. Dynamic contact angle, atomic force microscopy, and scanning electron microscopy were used to monitor the layer accumulation. siRNA loaded in the film was quantitated and the release profile of film in phosphate-buffered saline was studied. In vitro knockdown effect and cytotoxicity evaluation of the film were investigated using H1299 human lung carcinoma cells expressing green fluorescent protein (GFP). The transfection of human osteoblast-like cell MG63 and H1299 were performed and the osteogenic differentiation of MG63 on LbL film was analyzed. The CS/siRNA nanoparticles exhibited nice size distribution. During formation of the film, the surface wettability, topography, and roughness were alternately changed, indicating successful adsorption of the individual layers. The scanning electron microscope images clearly demonstrated the hybrid structure between CS/siRNA nanoparticles and sodium hyaluronate polymer. The cumulated load of siRNA increased linearly with the bilayer number and, more importantly, a gradual release of the film allowed the siRNA to be maintained on the titanium surface over approximately 1 week. In vitro transfection revealed that the LbL film-associated siRNA could consistently suppress GFP expression in H1299 without showing significant cytotoxicity. The LbL film loading with osteogenic siRNA could dramatically increase the osteogenic differentiation in MG63. In conclusion, LbL technology can potentially modify titanium surfaces with specific gene-regulatory siRNAs to enhance biofunction.Keywords: sustained gene silencing, osteogenic differentiation, chitosan, small interfering RNA, titanium